Interaction of the bacteriophage phi 29 protein p6 with double-stranded DNA. - Prieto, I (1988)
The Bacillus subtilis bacteriophage phi 29 protein p6 binds to double-stranded DNA, but not to single-stranded DNA, as determined by a gel retardation assay. The nature of the interaction was further studied by DNase I "footprinting" experiments. Protein p6 binds to fragments containing the right or left terminal sequences of phi 29 DNA, producing a characteristic pattern of hypersensitive bands spaced about 24 nucleotides apart along most of the fragment, flanking protected regions. Binding of protein p6 to an internal phi 29 DNA fragment was also observed, but the footprint pattern was more salt sensitive than that obtained with the terminal phi 29 DNA fragments. By electron microscopy, protein p6 was shown to cover the DNA, totally or partially, from one end. In addition, binding of protein p6 to relaxed circular DNA induced positive supercoiling, indicating that a topological change in the DNA occurred.